A Review of Agent Emotion Architectures - Slater, Stuart Ian; Moreton, Robert; Buckley, Kevan; Bridges, Andrew (Eludamos: Journal for Computer Game Culture, 2008)
<!--[if gte mso 9]> Normal 0 21 MicrosoftInternetExplorer4 <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:Times; panose-1:2 2 6 3 5 4 5 2 3 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:536902279 -2147483648 8 0 511 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:EN-GB; mso-fareast-language:EN-GB;} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 70.85pt 2.0cm 70.85pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]-->This paper attempts to highlight some of the research that has been conducted worldwide in the area of computational models of emotions, with a particular emphasis on agent emotions suitable for simulations and games. The intended outcome is to both review some of the more prominent research in the field, and to also ascertain the level of formal psychology that may underpin such work with a view to proposing that there is scope for an architecture built from the ground up, that arises from non-conflicting theories of emotion.